Matrix Photochemical Study and Conformational Analysis of CH3C(O)NCS and CF3C(O)NCS - Ramos, Luis A. (2014)
The vapor of acetyl isocyanide, CH3C(O)NCS, and trifluoroacetyl isocyanide, CF3C(O)NCS, were isolated in solid Ar at 15 K. The existence of rotational isomerism was confirmed when the matrixes were irradiated with broad-band UV−vis light (200 ≤ λ ≤ 800 nm) and also by temperaturedependent Ar-matrix IR spectroscopy. The initial spectra showed the vapor of CH3C(O)NCS and CF3C(O)NCS consist of two conformers syn−syn and syn−anti (with the CO bond syn with respect to the C−H or C−F bond and syn or anti with respect to the NC double bond). When CH3C(O)NCS is irradiated, simultaneously with the randomization process, H2CCO and HSCN are produced. In the case of the photolysis of CF3C(O)NCS, the main products are CF3NCS and CO. The assignment of the IR bands to the different photoproducts was made on the basis of the usual criteria, taking account reported antecedents in the literature.